Characterization and molecular epidemiology of extensively prevalent nosocomial isolates of drug-resistant klebsiella pneumoniae - Emerson Ribeiro Lima (2022)
FAPEMIG - Fundação de Amparo à Pesquisa do Estado de Minas Gerais